A mean-field homogenisation scheme with CZM-based interfaces describing progressive inclusions debonding. (1st December 2019) - Gentieu, Timothée; Catapano, Anita; Jumel, Julien; Broughton, James
Abstract: The objective of the present study is to describe the progressive debonding of inclusions in particle or fibre reinforced composites. To do so, the mean-field homogenisation scheme of Mori-Tanaka is enriched to take into account imperfect interfaces. The interfaces are modelled by a bilinear Cohesive Zone Model (CZM) taking into account normal and tangential effects. Results obtained with this new mean-field homogenisation scheme are compared to 2D FE-based numerical simulations that are used as reference results. The effects of inclusions volume fraction and size are also observed.